The deduction of fine structural details of reverse osmosis hollow fiber membranes using surface force-pore flow model - Idris, Ani; Ismail, Ahmad Fauzi; Shilton, Simon J.; Rashid, Roslina; Musa, M. (Elsevier Science B.V., 2002)
In order to elucidate the relationship between the dope extrusion shear rate and membrane performance, sodium chloride transfer through the asymmetric cellulose acetate reverse osmosis hollow fiber membranes is modeled, allowing fine details of the fiber structure to be deduced from the NaCl–H2O rejection characteristics. The structural information such as the pore size radius and skin thickness of the active layer deduced from the sodium chloride separation experimental data and surface force–pore flow model (SF–PF) is then used to interpret the relationship between the rheological conditions during spinning and membrane performance. The modeling results revealed that increased extrusion shear rate would decrease both pore size and thickness of the active layer, thus increasing the separation performance of the RO hollow fiber membranes.